Iron-Induced Susceptibility Effect at the Globus Pallidus Causes Underestimation of Flow and Volume on Dynamic Susceptibility Contrast-Enhanced MR Perfusion Images - Yamada, Kei; Gonzalez, R. Gilberto; Østergaard, Leif; Komili, Suzanne; Weisskoff, Robert M.; Rosen, Bruce R.; Koroshetz, Walter J.; Nishimura, Tsunehiko; Sorensen, A. Gregory (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: Age-related iron accumulation in extrapyramidal nuclei causes T2 shortening, which may result in decreased signal intensity in these areas on MR images. Because the dynamic susceptibility contrast-enhanced technique uses heavily T2*- or T2-weighted images, the iron-induced susceptibility may have direct impact on perfusion imaging. The purpose of this study was to assess the effect of iron-induced susceptibility on the calculated perfusion parameters. The difference of this effect between gradient-echo and spin-echo sequences was also assessed.METHODS: Dynamic susceptibility contrast-enhanced MR perfusion imaging data of 12 patients were used for this study. Perfusion images were obtained using a single shot spin-echo echo-planar imaging sequence in seven patients and a gradient-echo echo-planar imaging sequence in five patients. Region of interest measurements of relative cerebral blood flow, relative cerebral blood volume, and mean transit time were obtained at various parts of the gray matter, including the globus pallidus, putamen, caudate nucleus, thalamus, and cerebral cortex of temporal, frontal, and occipital lobes. The baseline signal intensity on the source images and the magnitude of signal change (ΔR2* or ΔR2) were also assessed.RESULTS: The globus pallidus had statistically significantly lower values of relative cerebral blood flow, relative cerebral blood volume, baseline signal intensity, and magnitude of signal change compared with other parts of the gray matter for both gradient-echo and spin-echo sequences (P < .05). Underestimations of these values were more prominent for the gradient-echo than for the spin-echo sequence. Little variance in the measured mean transit time was noted.CONCLUSION: Iron-induced susceptibility effect may lead to underestimation of relative cerebral blood flow and relative cerebral blood volume in the basal ganglia.